A heavy metal P-type ATPase OsHMA4 prevents copper accumulation in rice grain - Huang, Xin-Yuan; Deng, Fenglin; Yamaji, Naoki; Pinson, Shannon R.M..; Fujii-Kashino, Miho; Danku, John; Douglas, Alex; Guerinot, Mary Lou; Salt, David E.; Ma, Jian Feng (Nature Publishing Group, 2016)
Rice is a major source of calories and mineral nutrients for over half the world’s human population. However, little is known in rice about the genetic basis of variation in accumulation of copper (Cu), an essential but potentially toxic nutrient. Here we identify OsHMA4 as the likely causal gene of a quantitative trait locus controlling Cu accumulation in rice grain. We provide evidence that OsHMA4 functions to sequester Cu into root vacuoles, limiting Cu accumulation in the grain. The difference in grain Cu accumulation is most likely attributed to a single amino acid substitution that leads to different OsHMA4 transport activity. The allele associated with low grain Cu was found in 67 of the 1,367 rice accessions investigated. Identification of natural allelic variation in OsHMA4 may facilitate the development of rice varieties with grain Cu concentrations tuned to both the concentration of Cu in the soil and dietary needs.